2016
DOI: 10.1002/joc.4621
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal trends in climatic variables in arid areas of northwest China

Abstract: The trends of major climatic variables at annual and seasonal scales over the past 51 years (1960–2010) in arid areas of northwest (NW) China are investigated using the Mann–Kendall test. From the results it is clear that the majority of the trends (more than 94%) showed significant increasing tendency in three annual temperature indices, including the mean temperature (Tmean), the mean minimum temperature (Tmin) and mean maximum temperature (Tmax). For Tmax, however, the significant increase was mainly the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
2
6
0
Order By: Relevance
“…The strong inter-annual variation in the annual precipitation series might be the reason for contrary results in previous studies based on different study periods. The negative trend in the summer accumulated precipitation series was also confirmed by other studies in Inner Mongolia (Geng et al, 2016;Hu et al, 2017), and this feature was consistent across the whole Mongolian Plateau in northeastern Asia (Qin et al, 2018). We further analyzed the regional summer accumulated precipitation series and the results showed no trend-shift features.…”
Section: Change Features In Inner Mongoliasupporting
confidence: 86%
See 1 more Smart Citation
“…The strong inter-annual variation in the annual precipitation series might be the reason for contrary results in previous studies based on different study periods. The negative trend in the summer accumulated precipitation series was also confirmed by other studies in Inner Mongolia (Geng et al, 2016;Hu et al, 2017), and this feature was consistent across the whole Mongolian Plateau in northeastern Asia (Qin et al, 2018). We further analyzed the regional summer accumulated precipitation series and the results showed no trend-shift features.…”
Section: Change Features In Inner Mongoliasupporting
confidence: 86%
“…Therefore, it is crucial to detect the detailed and accurate change features of the time-series of precipitation and temperature datasets in Inner Mongolia. Previous studies mainly focused on the overall trend analysis of these two variables and contrary results were found in different studies, e.g., Hu et al (2015) found that Inner Mongolia became warmer-drier from 1961 to 2012, while others demonstrated a warmer-wetter trend (Geng et al, 2016;Hu et al, 2017;Qin et al, 2018). Meanwhile, the trend-shift features in the time-series of precipitation and temperature in Inner Mongolia are interesting but have rarely been analyzed.…”
Section: Introductionmentioning
confidence: 89%
“…Discrepancies in the trend magnitudes are likely caused by different regional extents, time periods, and data sources. This methodological constraint might also affect the results of other Central Asian studies [3,5,65,66], and global studies [67], as their time series also show an abrupt change of the mean in the late 20th century. It can be summarized that, despite different time periods and different datasets, all large-scale studies agreed on a strong warming trend averaged over Central Asia, which has accelerated in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Inhomogeneities in station data records can be due to observational routines (station relocations or changes in measuring techniques) and in that case, statistical methods and metadata information are effective for identifying these [2]. However, some shifts in climate dynamics are a consequence of human activities [3][4][5], or are related to El-Niño Southern Oscillation (ENSO) events such as those that occurred in 1976-77 [6], or to volcanic eruptions and changes in atmospheric composition and circulation [7].…”
Section: Introductionmentioning
confidence: 99%